How Valuable Are Organic Amendments as Tools for the Phytomanagement of Degraded Soils? The Knowns, Known Unknowns, and Unknowns - Gómez-Sagasti, María T.; Hernández, Antonio; Artetxe, Unai; Garbisu, Carlos; Becerril, José M. (Frontiers in Sustainable Food Systems, 2018)
Nowadays, soil functionality and productivity are severely impaired due, in great part, to the fact that most of the land is being intensively used for food production and urbanization purposes, with a consequent rise in the generation of wastes and consumption/degradation of fertile soils. These issues can be jointly addressed by an integrated and sustainable management of the soil resource carried out in the framework of two recent paradigms: circular economy and phytomanagement. Within the fields of resource conservation and regenerative (urban) land management, at least the three following fundamental aspects can be contemplated: (i) the valorization and safe recovery of organic wastes (e.g., composts, green and animal manures, and biosolids) as soil amendments (from residue to resource); (ii) the re-development and revegetation of degraded soils characterized by low organic matter content, deficient physical structure and depressed biological status (from bare to vegetated soil); and, finally, (iii) the promotion of soil health in order to support soil ecological processes, functions and concomitant ecosystem services (integration of ecocentric and anthropocentric perspectives). Here, we discuss the benefits (knowns), potential risks (known unknowns) and future/affordable uncertainties (unknowns) resulting from the application of organic amendments (OAs) to soil. Traditionally, most studies have used physical-chemical parameters to assess soil health/quality, whereas less attention has been paid to soil biological criteria. Thus, we highlight the relevance of soil biological properties as key drivers of ecological restoration and suitable indicators of soil health. Notwithstanding, special attention should be paid to “amendments-plants-microorganisms” interactions in different soils and field conditions. Finally, the risk of introduction of emerging contaminants, including for instance microplastics and antibiotic resistance genes (ARGs), through the application of OAs to soil, is currently a matter of much concern that must urgently be addressed if we are to continue with such practice.